Antibacterial activity of 5-chloro substituted phenyl n-acylhydrazones with aromatic substitution at ortho- and para-directors as potent adjuvants - Chan, Yao Xiang (2024)
The emergence of antimicrobial-resistant pathogens has led to a decline in the availability of effective medications for clinical use, which urges the development of new drugs. N-acylhydrazone (NAH) with its versatile chemical moiety becomes essential in designing new drugs as its derivatives have been approved as therapeutics. This project studied the in vitro antibacterial activity of 7 NAH derivative compounds with different aromatic substitutions at ortho and para directors individually and in combination with 3 standard drugs as adjuvants against 8 bacterial strains using the broth microdilution method to determine Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC). The results revealed that Compounds 1 (2-Br), 4 (H), 6 (2-OCH3) and 7 (2,4-Cl2) exhibited moderately active antibacterial activity against Staphylococcus aureus (ATCC 6538) with a MIC value of 62.5 μg/mL, showing species-specific antibacterial activity. With the combination of antibiotics as adjuvants, the NAH derivative compounds demonstrated enhanced antibacterial activities. Notably, the ciprofloxacin-NAH adjuvant combinations obtained MBC/MIC ratio ranging from 1 to 4, suggesting the bactericidal effects. Nevertheless, the Fractional Inhibitory Concentration (FIC) index calculated revealed that neither of the antibiotic-NAH adjuvant combinations was suitable for further studies although synergism was observed because most of the combinations recorded insignificant interactions, indicating the antibacterial activity was contributed by the antibiotic itself.